Volcano ([S.l.] Sequoia Entertainment, 1997)
This documentary looks at the study of volcanoes, and shows some of the worst volcanic eruptions in recent history.
An Adrenaline Production in association with the Learning Channel.
VCD.
Produced and written by Kathleen Phelan.
Keywords: Volcanoes -- Hawaii; Volcanoes -- United States; Volcanoes -- Colombia; Volcanoes -- Iceland; Volcanoes -- Papua New Guinea; Volcanoes -- Montserrat; Volcanoes -- Philippines